A circRNA signature predicts postoperative recurrence in stage II/III colon cancer. Issue 10 (2nd September 2019) - Ju, Huai‐Qiang; Zhao, Qi; Wang, Feng; Lan, Ping; Wang, Zixian; Zuo, Zhi‐Xiang; Wu, Qi‐Nian; Fan, Xin‐Juan; Mo, Hai‐Yu; Chen, Li; Li, Ting; Ren, Chao; et al.
Abstract: Accurate risk stratification for patients with stage II/III colon cancer is pivotal for postoperative treatment decisions. Here, we aimed to identify and validate a circRNA‐based signature that could improve postoperative prognostic stratification for these patients. In current retrospective analysis, we included 667 patients with R0 resected stage II/III colon cancer. Using RNA‐seq analysis of 20 paired frozen tissues collected postoperation, we profiled differential circRNA expression between patients with and without recurrence, followed by quantitative validation. With clinical information, we generated a four‐circRNA‐based cirScore to classify patients into high‐risk and low‐risk groups in the training cohort. The patients with high cirScores in the training cohort had a shorter disease‐free survival (DFS) and overall survival (OS) than patients with low cirScores. The prognostic capacity of the classifier was validated in the internal and external cohorts. Loss‐of‐function assays indicated that the selected circRNAs played functional roles in colon cancer progression. Overall, our four‐circRNA‐based classifier is a reliable prognostic tool for postoperative disease recurrence in patients with stage II/III colon cancer. Synopsis: Novel molecular biomarkers allowing for better prognostic stratification of patients with stage II/III colon cancer are urgently needed. In this study, a circRNA‐based signature (cirScore) was identified and validated to improve postoperative risk‐stratification for these patients. Dysregulated circRNAs showed strong classification capacities in distinguishing between recurrent and nonrecurrent colon cancer patients. The proposed four‐cirRNA‐based cirScore can effectively classify patients with stage II/III colon cancer into groups with low and high risks of disease recurrence. The loss‐of‐function assay indicated that the representative circRNAs plays functional roles in the sophisticated regulation of colon cancer progression. Nomograms incorporating the cirScore with existing risk factors achieved excellent accuracy for predicting disease‐free and overall survival for patients with stage II/III colon cancer. Abstract : Novel molecular biomarkers allowing for better prognostic stratification of patients with stage II/III colon cancer are urgently needed. In this study, a circRNA‐based signature (cirScore) was identified and validated to improve postoperative risk‐stratification for these patients.